Short-term movements of the Pig-Nosed Turtle (Carrettochelys insculpta) in the Kao River, South Papua, Indonesia - Sawaki, Morgan Wayne Luther; Kusrini, Mirza Dikari; Prasetyo, Lilik Budi; Ramdani Manurung (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Understanding animal movement is essential for assessing species' ecological needs and informing effective conservation strategies. This study investigates the short-term daily movement and home range of the Endangered (EN) pig-nosed turtle (Carettochelys insculpta) in the Kao River, Boven Digoel District, South Papua, Indonesia. Native to Papua New Guinea, Northern Australia, and Southern Papua, this freshwater turtle faces heavy egg harvesting pressure. Using low-cost GPS tracking devices, we monitored six adult individuals (one male and five females) over a three-day period during November–December 2023. The results indicated that the daily movements of C. insculpta ranged from 84.95 to 648.77 m. Average home range estimates were 18.03 ha (minimum convex polygon), 7.51 ha (50% kernel density), and 12.44 ha (95% kernel density). The movement overlaps among the four turtles totaled 30.64 ha, with an average overlap of 6.12 ha. The hotspot analysis identified 76.16 ha as key movement areas, revealing that the pig-nosed turtles tend to stay near sandbanks, primary dryland forest, secondary dryland forest, and shrublands. Our studyprovides important baseline ecological data that can be used to inform future conservation and recovery programs. Elaboration between stakeholders and the local community can be carried out to protect the species.